Titanium oxide nanoparticles as additives in engine oil - Meena Laad; Vijay Kumar S. Jatti (Journal of King Saud University: Engineering Sciences)
This research study investigates the tribological behaviour of titanium oxide (TiO2) nanoparticles as additives in mineral based multi-grade engine oil. All tests were performed under variable load and varying concentrations of nanoparticles in lubricating oil. The friction and wear experiments were performed using pin-on-disc tribotester. This study shows that mixing of TiO2 nanoparticles in engine oil significantly reduces the friction and wear rate and hence improves the lubricating properties of engine oil. The dispersion analysis of TiO2 nanoparticles in lubricating oil using UV spectrometer confirms that TiO2 nanoparticles possess good stability and solubility in the lubricant and improve the lubricating properties of the engine oil. Keywords: Titanium oxide, Nanoparticles, UV spectrometer, Tribotester, Engine oil